2005
DOI: 10.1093/brain/awh402
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological differences between musician's dystonia and writer's cramp

Abstract: Focal hand dystonia (FHD) has been suggested to be a maladaptive response of the brain to repetitive performance of stereotyped and attentionally demanding hand movements. However, not all patients with FHD have a strict history of excessive hand use; for example, patients with musician's dystonia (MD) spend many hours per day with their attention focused on instrumental practice, whereas many patients with writer's cramp (WC) have a history of average hand use. The present experiments test whether seven MD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
120
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 55 publications
12
120
3
2
Order By: Relevance
“…Recent studies comparing MD and WC patients using transcranial magnetic stimulation suggested pathophysiologic differences between the two conditions. 16,17 Given a possible common genetic cause of MD and WC in at least a subset of patients as confirmed by the present study, however, these neurophysiologic differences could be interpreted as a secondary rather than a primary phenomenon.…”
Section: Patients and Familiessupporting
confidence: 59%
“…Recent studies comparing MD and WC patients using transcranial magnetic stimulation suggested pathophysiologic differences between the two conditions. 16,17 Given a possible common genetic cause of MD and WC in at least a subset of patients as confirmed by the present study, however, these neurophysiologic differences could be interpreted as a secondary rather than a primary phenomenon.…”
Section: Patients and Familiessupporting
confidence: 59%
“…This change is larger than after a single session of motor practice in which inputs expanded only to the directly adjacent muscle (Rosenkranz and Rothwell, 2006). A loss of the usual inhibitory effect of muscle vibration onto nonvibrated hand muscles has been described in focal hand dystonia (Rosenkranz et al, 2005). However, in the present case, it should be noted that the loss of inhibition is input specific and only apparent for proprioceptive input from the trained APB.…”
Section: Discussioncontrasting
confidence: 44%
“…The steep slope of the SICIcurve in musicians may allow more effective control of enhanced plasticity and benefit performance. This might be not the case in focal dystonia, because some studies have described reduced SICI at rest (Ridding et al, 1995;Gilio et al, 2003), although this finding is inconsistent (Stinear and Byblow, 2004a,b;Butefisch et al, 2005;Rosenkranz et al, 2005).…”
Section: Beneficial Versus Maladaptive?mentioning
confidence: 99%